Effectiveness of Training for Teachers in Early Identification of Skin Disorders Among Primary School Attending Children - A Quasi-Experimental Study Protocol - Palanivel, Nirmaladevi; Kandasamy, Sunitha; Sundararaju, Sangeetha; Subbiah, Padmavathi; Govindraj, Abirami; Gopal, Muthu; Jeyaraman, Yuvaraj; Kalyanaraman, Shantaraman (National Journal of Community Medicine, 2022)
Skin diseases are the leading cause of morbidity in children. As children spend most of their time in schools, training teachers on the detection of skin changes and timely referral will prevent or reduce the complications. Hence, we propose a quasi-experimental study to evaluate the effectiveness of training for teachers in the early identification of skin disorders among primary school children in a rural area of southern India. The teachers of government and government-aided schools in the field practice area of Model Rural Health Research Unit, Tirunelveli, will be the intervention group. The teachers of the same schools in the nearby village will be the control group. The investigators and the National Institute of Epidemiology, ICMR, Chennai, will develop and validate the training manual. Using the manual, the principal investigator will train the teachers on identifying and referring skin changes and provide a training manual, model register, and referral slip to each teacher. The investigators will review the schools quarterly and collect the number of children identified and referred from both groups before and after the intervention. Thus, the trained teachers will be a resource to achieve the objectives of the school health program, complementing the health services.